2008
DOI: 10.1007/s10658-008-9306-1
|View full text |Cite
|
Sign up to set email alerts
|

Germination of Fusarium oxysporum in root exudates from tomato plants challenged with different Fusarium oxysporum strains

Abstract: The response of microconidia from pathogenic and non-pathogenic Fusarium oxysporum to root exudates from tomato plants inoculated with different pathogenic and non-pathogenic F. oxysporum strains was studied. Root exudates from non-inoculated tomatoes highly stimulated the microconidial germination of the two tomato pathogens, F. oxysporum f.sp. lycopersici strain Fol 007 and F. oxysporum f.sp. radicis-lycopersici strain Forl 101587. In root exudates from tomato plants challenged with the pathogen Fol 007 the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 25 publications
0
32
0
4
Order By: Relevance
“…On the other hand, nonsignificant differences were observed in mycelial growth in exudates from plants grown in 'GWB comp ' treatment either inoculated or un-inoculated. Together with biochar and compost tomato roots upon infection with F. oxysporum influenced the composition of root exudates probably because of exudation of new compounds or by altering the composition of root exudates (Akhter et al 2015;Steinkellner et al 2008;Benhamou 1991). The level of sugar contents and secondary metabolites such as flavonoids in the root exudates varies during tomato-Fol interaction which ultimately plays a role in stimulating or supressing the mycelial growth and development (Hage-Ahmed et al 2013;Steinkellner and Mammerler 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, nonsignificant differences were observed in mycelial growth in exudates from plants grown in 'GWB comp ' treatment either inoculated or un-inoculated. Together with biochar and compost tomato roots upon infection with F. oxysporum influenced the composition of root exudates probably because of exudation of new compounds or by altering the composition of root exudates (Akhter et al 2015;Steinkellner et al 2008;Benhamou 1991). The level of sugar contents and secondary metabolites such as flavonoids in the root exudates varies during tomato-Fol interaction which ultimately plays a role in stimulating or supressing the mycelial growth and development (Hage-Ahmed et al 2013;Steinkellner and Mammerler 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The liquid fraction was filtered through three layers of fleece cloth filters (150 μm). The concentration of microconidial suspension was adjusted according to Steinkellner et al (2008).…”
Section: Fungal Inoculum Productionmentioning
confidence: 99%
“…The greatest influence on the formation of microorganisms communities in the soil is exerted by plants through their roots exudates or hulling root cells (Steinkellner et al 2008, Jaroszuk-Ściseł et al 2009). Root exudates stimulate or inhibit the development of soil plant pathogens and they increase the population of antagonistic microorganisms.…”
mentioning
confidence: 99%
“…However, there are indications for a specific effect of the compounds found in tomato root exudates, and it has been reported that the germination rate of several F. oxysporum strains is affected differently by tomato root exudates (Steinkellner et al, 2008). No differences in the mycelial development of F. oxysporum have been observed in the vicinity of tomato and wheat roots, such that non-host plants can function as symptomless carriers of fusarium wilt (Steinberg et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The purity of the fungal isolates was verified by monosporal cultures on PDA plates, using microscopic observations of the microconidia and macroconidia in addition to the stability of the cultural characteristics (colony shape, coloration and morphometric dimensions). The conidial suspensions were prepared as described by Steinkellner et al (2008) with some modifications: the PDA fungal culture plates (eight days old, incubated at 28°C) were flooded with 2 ml sdH2O and scraped into 48 ml sdH2O. The microconidia suspensions obtained were filtered through six layers of sterile cheesecloth to separate the mycelium from the conidia and adjusted by a hemocytometer to 10 6 microconidia/ml.…”
Section: Plant Pathogensmentioning
confidence: 99%